2011
DOI: 10.1007/s00228-011-1080-x
|View full text |Cite
|
Sign up to set email alerts
|

Near-fatal tramadol cardiotoxicity in a CYP2D6 ultrarapid metabolizer

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 19 publications
2
41
0
Order By: Relevance
“…A few cases of ultra-rapid metabolizers can be found in the literature, both for the paediatric population [3] and for adults [24,25]. In 6 of our cases, we had a history of drug overdose but in one case (case n°6), no clear explanation was found after parental questioning.…”
Section: Discussionmentioning
confidence: 66%
“…A few cases of ultra-rapid metabolizers can be found in the literature, both for the paediatric population [3] and for adults [24,25]. In 6 of our cases, we had a history of drug overdose but in one case (case n°6), no clear explanation was found after parental questioning.…”
Section: Discussionmentioning
confidence: 66%
“…CYP2D6 plays a pivotal role in the pharmacokinetics and analgesic efficacy of tramadol. Several reduced or none functional CYP2D6 alleles as well as alleles with multiple gene copies have significant impacts on clinical outcome in patients under tramadol medication [22,24,27,33,45,5155]. Pharmacokinetic studies have shown that the impact of CYP2D6 phenotypes on tramadol pharmacokinetics was similar after single oral, multiple oral, or intravenous administrations [33,52,55].…”
Section: Pharmacogenomicsmentioning
confidence: 99%
“…Severe life-threatening adverse events were reported in two case reports. One patient with renal impairment carrying the CYP2D6 gene duplication experienced respiratory depression [45] and another UM developed a near-fatal cardiotoxicity, in both cases because of tramadol use [51]. …”
Section: Pharmacogenomicsmentioning
confidence: 99%
“…On the other hand, loss of therapeutic efficacy at standard doses can also be observed in UMs since the drug metabolization occurs at a fast rate (Davis & Homsi 2001). Finally, UM may also present either improved therapeutic efficacy or more frequently severe adverse effects, due to a higher rate of toxic metabolites formation (Kirchheiner et al 2008;Elkalioubie et al 2011). …”
Section: Lessons From Phase I and Ii Reactionsmentioning
confidence: 99%